Teaching Dynamics, Public Speaking Anxiety, and Language Proficiency of Student Interns - Lava, Sharmaine L. (Future Science / FSH-PH Publications, 2025)
This mixed-method research aimed to evaluate the teaching dynamics, public speaking anxiety, and language proficiency of student interns in Capiz during the Academic Year 2023-2024. A sample of 300 student interns, drawn from a total population of 1,137 across various teacher education programs, participated in the study. Additionally, nine teacher mentors, an internship supervisor, and nine student interns from Higher Education Institutions in Capiz were involved in the quali-tative component. Data collection employed a researcher-constructed questionnaire and focus group discussion guide, addressing variables such as teaching dynamics, public speaking anxiety, and language pro-ficiency. Statistical tools used included mean, standard deviation, ANOVA, and Pearson correlation coefficient, with an alpha level set at .05. The findings revealed that student interns demonstrated a